The Development of Web-Based Learning Media on Western Bridal Make-Up Subject - Thaitami, Siti Hajar; Maksum, Hasan (Universitas Pendidikan Ganesha, 2020)
Internet-based educational facilities can be used as a means of delivering learning that relies on practical aspects and is easily accessible anywhere and anytime. In addition, this learning media enables distance learning or the delivery of information between lecturers and students. Western Bridal Make Up is a compulsory subject in an education program. This study aims to a) develop web-based learning media products on database materials for the Department of Makeup and Beauty Education at Universitas Negeri Padang through the process of developing media, b) obtain information about the feasibility of web-based learning media products on database materials used as support in database learning in the Department of Makeup and Beauty Education, Universitas Negeri Padang.This research uses alpha testing method (alpha testing). The research subjects in alpha testing were 2 media experts and 2 material experts, while the research subjects in beta testing were 20 students majoring in Makeup and Beauty Education, Padang State University. Data obtained by using test instruments to test the effectiveness and non-test instruments to test the validity and practicality in the research process. Based on the results of the developed learning media produces valid media in terms of media (design) with a value of 0.918 and valid from the material side with a value of 0.875 by media experts and material experts and from the practical side of the media developed has a practical level of practicality with a percentage of 95%, from the beta test obtained 100% very feasible. The implications of the application of this media can increase the use of instructional media as teaching material that is independent, mobile, and interactive by lecturers, thus helping lecturers in delivering learning material.